2021
DOI: 10.1371/journal.pone.0253408
|View full text |Cite|
|
Sign up to set email alerts
|

Operative treatment of fragility fractures of the pelvis is connected with lower mortality. A single institution experience

Abstract: Background Fragility fractures of the pelvis (FFP) represent an increasing clinical entity. Until today, there are no guidelines for treatment of FFP. In our center, recommendation for operative treatment was given to all patients, who suffered an FFP type III and IV and to patients with an FFP type IIwith unsuccessful non-operative treatment. We performed a retrospective observational study and investigated differences between fracture classes and management alternatives. We hypothetized that operative treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
(34 reference statements)
2
16
1
Order By: Relevance
“…Besides, an incorrect classification of FFP II by the observer, the observer might decide to not follow the recommendations of Rommens and Hofmann 9 . This might be the result of current studies showing a decreased rate of mortality 51 , rate of general complications for percutaneous procedures 52 and an improved mobility following operative therapy 53 . This data underlines the need to introduce additional modifiers for treatment decision (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Besides, an incorrect classification of FFP II by the observer, the observer might decide to not follow the recommendations of Rommens and Hofmann 9 . This might be the result of current studies showing a decreased rate of mortality 51 , rate of general complications for percutaneous procedures 52 and an improved mobility following operative therapy 53 . This data underlines the need to introduce additional modifiers for treatment decision (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Hoech et al [74] found a signi cantly higher survival rate for surgically treated patients of 21% compared to conservatively treated patients over a two-year period. With a comparable distribution of FFP types, Rommens et al [75] also found a lower mortality in surgically treated patients.…”
Section: Outcome Considering Complications and Mortalitymentioning
confidence: 86%
“…The study concluded that operative treatment of FFP resulted in lower mortality rates ( P <0.001), although longer length of stay ( P <0.001) and more in hospital complications ( P =0.006) were observed in the operative group 29) . Patients in the non-operative group had greater mobility and independence at discharge ( P <0.001); however, comparable quality of life was observed between the groups 29) .…”
Section: Treatment Optionsmentioning
confidence: 91%
“…Unfortunately, data for evaluation of the outcomes of conservative management is limited; however, new studies are emerging. In a recent study reported in 2021, Rommens et al 29) conducted a retrospective comparison of operative vs. conservative management for FFP types II, III, and IV in 238 patients; 100 of these patients received conservative treatment. The study concluded that operative treatment of FFP resulted in lower mortality rates ( P <0.001), although longer length of stay ( P <0.001) and more in hospital complications ( P =0.006) were observed in the operative group 29) .…”
Section: Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation